Anti-Inflammatory Impact of Minocycline in a Mouse Model of Tauopathy - Garwood, Claire J.; Cooper, Jonathan D.; Hanger, Diane P.; Noble, Wendy (Frontiers in Psychiatry, 2010)
Alzheimer’s disease (AD) is characterised by the extracellular deposition of β-amyloid in senile plaques, the intraneuronal accumulation of hyperphosphorylated tau aggregates as neurofibrillary tangles, and progressive neuronal loss leading to the onset of dementia. Increasing evidence suggests that neuroinflammatory processes contribute to the progression of AD. Minocycline is a semi-synthetic tetracycline derivative commonly used in the treatment of acne. Many studies have revealed that minocycline also has potent anti-inflammatory actions that are neuroprotective in rodent models of Huntington’s disease, Parkinson’s disease and motor neuron disease. Recently, we demonstrated that minocycline reduces the development of abnormal tau species in the htau mouse model of Alzheimer’s disease. We have now extended these findings by examining the impact of minocycline on inflammatory processes in htau mice. Immunohistochemical analysis revealed that minocycline treatment resulted in fewer activated astrocytes in several cortical regions of htau mice, but did not affect astrocytosis in the hippocampus. We found htau mice have significantly elevated amounts of several cortical pro-inflammatory cytokines. In addition, we find that minocycline treatment significantly reduced the amounts of several inflammatory factors, including monocyte chemoattractant proteins 1 and 5, interleukins -6 and -10, eotaxin, and I-309. Furthermore, the reduced amounts of these cytokines significantly correlated with the amount of tau phosphorylated at Ser396/404 in the cortex of htau mice. These results may reveal new cytokine targets of minocycline that could be associated with its inhibition of tau pathology development in vivo. It is possible that further investigation of the role of these cytokines in neurodegenerative processes may identify novel therapeutic targets for Alzheimer’s disease and related disorders.